Clinical Presentation of Foramen Magnum Meningioma Masqueraded by Carpal Tunnel Syndrome: A Report of 2 Cases. Issue 4 (October 2021) - Bahrami, Eshagh; Parvaresh, Mansour; Fattahi, Arash; Farzan, Abdolnaser; Kazemi, Foad
Abstract : Case: Meningioma is the second most common intracranial tumor. We present 2 cases of foramen magnum meningioma (FMM) that was first operated on with the diagnosis of carpal tunnel syndrome (CTS). Conclusion: During the diagnostic assessment of CTS and recalcitrant CTS, a more proximal etiology of nerve compression should be considered, including FMM. If a more proximal cause of nerve dysfunction is suspected, cervical spine magnetic resonance imaging may be beneficial to evaluate a patient for spinal etiology.